SPIRITUALIZING TECHNOLOGY: OPEN DIALOGUE ACROSS FAITHS IN “LOG IN” ON CLOSE THE DOOR DEDDY CORBUZIER’S YOUTUBE CHANNEL - Suatin, Ricka Milla; Susanti, Dwi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
Podcast content is very diverse, one of which is a da'wah podcast called